ANALISIS REFERENSI PADA JURNAL ILMU DAN TEKNOLOGI KAYU TROPIS TAHUN 2013 – 2017 - Ningsih Maha, Rahmadani; Tupan, Tupan (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2019)
Reference analysis of articles in online journals was conducted, namely Jurnal Ilmu dan Teknologi Kayu Tropis in 2013 – 2017. The study aims to: (1) find out the distribution of articles and references based on years; (2) know the reference composition based on the type of document; (3) know the patterns of authorship in reference; (4) know the update of the reference year; (5) find out the ranking of journals that are used as references; (6) know the authorship affiliation pattern. The research was carried out by descriptive method. Data was taken from the Journal of Tropical Wood Science and Technology for five years (2013-2017). Data collection was conducted in October 2018 from the journal webpage available at http://ejournalmapeki.org/index.php/JITKT. Details of each article published , such as the number of articles in each journal number, article distribution, authorship patterns for each article have been recorded and analyzed to make observations.The collected data was compiled and analyzed using an MS-Excel spreadsheet.The results showed that the average number of articles per year was 20,2 and and references per year is 385,8. The highest reference composition is articles totaling 1063, around 55,11 %.The pattern of authorship shows that more than half of writers prefer to work in collaboration because 51,44% of citations are multi-authors, while 48,56% of writers prefer to work in isolation, more reference skills in the span of 0-10 years (current category) namely as many as 1.108 citations/references and 821 citations/references classified as not up-to-date, namely over ten years as many as 821 citations / references. The most used ranking reference journal used by the author was taken from the Journal of Tropical Wood Technology.